Improving Students’ Reading Ability in Guessing Word Meaning from Context through Guided Discovery Learning: A Classroom Action Research on the Eleventh Grade Students of SMAN 1 Sumpiuh in the Academic Year 2019/2020 - Tri Wahyuni (English Language and Education Spectrum, 2022)
This action research aimed to investigate how Guided Discovery Learning can be implemented to improve the students’ ability in guessing word meanings from context as well as the strengths and weaknesses of the method when used in class. The research participants were the students of SMA Negeri 1 Sumpiuh, XI Science 4. The researcher implemented two cycles in this research and four steps for each cycle; planning, action, observation, and reflection. The data were obtained from several techniques, including tests, observation, questionnaires, and interviews. To analyse the quantitative data, the researcher applied descriptive statistics, comprising the following dimensions: highest and lowest scores and means. The researcher analysed the improvement of the students’ ability through interviews and questionnaires to analyse the qualitative data. The research findings show that the student problems related to difficult words could be solved by predicting their meanings from context. This skill could help the students understand and comprehend the text easily without depending on the dictionary or asking the meanings of the unknown words to other people. Therefore, a certain method was needed to develop the students’ skills in guessing word meanings from context, one of which is Guided Discovery Learning (GDL). In conclusion, using GDL allowed the students to discover signal words to determine the meaning of the unknown words. However, GDL has its strengths and weaknesses, although it is recommended for teachers, particularly when teaching reading and vocabulary.